Integrating Pre-service Teacher Training with 21st Century Skills: A Global Classroom Perspective - Farikha, Ninik; Prasongko, Angga; Lestari, Pritanti Yuni; Hamida, Ulfi Dina (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Kadiri, 2025)
This study aims to analyze how the pre-service teacher training program in the English Education Program, Faculty of Teacher Training and Education, Islamic University of Kadiri (UNISKA) Kediri, facilitates the development of 21st-century skills and the extent to which students' teaching practices align with the needs of learners. A qualitative method and descriptive approach were implemented. Data were collected through in-depth interviews, classroom observations, and document analysis. The study found that the integration of 21st-century skills in the pre-service teacher training at UNISKA has started to be implemented, particularly through microteaching courses and the School Environment Introduction (PLP) program. Findings indicate a gap between the training design and classroom practices. Students are capable of using technology and engaging in creative activities, but they still face challenges such as limited facilities, time constraints, and a conventional school culture. On the other hand, students who received reflective guidance from lecturers and mentor teachers demonstrated high adaptability in managing classrooms and integrating technology according to the context. The findings emphasize that the success of 21st-century teacher training is greatly influenced by three key factors: a practice-based reflective training design, collaborative mentor support, and a learning environment that fosters innovation. It can be concluded that the pre-service teacher training at UNISKA is moving toward the 21st-century education paradigm, although it still requires systemic strengthening. This outcome is expected to serve as a foundation for the development of a more contextual, reflective, and adaptive teacher training curriculum that meets the needs of contemporary learners.